ANALISIS ECONOMIC VALUE ADDED (EVA) SEBAGAI ALAT PENGUKUR KINERJA KEUANGAN PADA PT INDOFOOD SUKSES MAKMUR TBK PERIODE 2020-2022 - I'zaz Saumi; Sumar'in; Maskupah (Cross-Border Journal of Business Management, 2026)
This research focuses on using the EVA method to measure the company's financial performance to see the company's economic added value. This study aims to analyze the company's financial performance by using the EVA (Economic Value Added) method in PT Indofood Sukses Makmur Tbk for the 2020-2022 financial report period. This research is a type of descriptive statistical type research with a quantitative approach. Where the population used is all the company income report of PT. Indofood Sukses Makmur Tbk and the sample taken from the company, namely the financial statements of PT. Indofood Suukses Makmur Tbk for the 2020-2022 period. The data collection uses secondary data, while the data analysis technique uses quantitative analysis with descriptive statistical properties and the Economic Value Added (EVA) method as a tool to measure financial performance at PT. Indofood Sukses Makmur Tbk for the 2020-2022 Period with the formula EVA = NOPAT – Capital Charges. Based on the results of the calculation of the EVA method in measuring financial performance at Indofood Sukses Makmur, Indofood had a diverse financial performance during the period. In 2020-2022, a positive EVA score indicates that the company has been able to provide economic added value, so that financial performance can be considered good. Using the EVA method, this study shows that PT Indofood Sukses Makmur Tbk. has a diverse financial performance during the period 2020-2022. A positive EVA score in 2020-2022 indicates good financial performance, This proves that EVA can be used as an effective tool to measure a company's financial performance.